Modification of personal life values through cognitive and behavioral counseling approaches - Noscal, Naomi Narvaez (2005)
The researcher used counseling and Survey for Personal Values in an experiment to find out if there would be modification of personal life values through the use of cognitive and behavioral approaches. The study revealed that the most preferred life values domain among the groups were "orderliness and goal orientation". The more effective approach in the modification of personal life values is behavioral approach.